Peningkatan Pemahaman Gizi Melalui Kegiatan Pengabdian Masyarakat: Mitos dan Fakta Gizi Sehari-Hari di SMK Citra Edukasi Bangsa - Salsabilah, Dinda; Asysyahiidah, Hasna Wafaa; Iswara, Meuthia Pramesti; Nabilah, Riska; Utami, Sabrina Ardina; Kusumaningati, Walliyana (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Myths surrounding nutrition are still widely believed by the community, especially among adolescents, affecting lifestyle and health improvement in the long term. Low nutritional literacy can impact long-term health improvement. Objective: To increase knowledge about nutrition, particularly among adolescents concerning facts and myths about nutrition in daily life. Method: This activity was conducted in June 2025 at SMK Citra Edukasi Bangsa in North Jakarta. It aimed to measure the increase in knowledge of facts and myths through pre- and post-tests. Then, interactive outreach was conducted using PPT, leaflets, and posters. Data analysis used a paired sample t-test. Result: There was a significant increase in students' knowledge (p-value = 0.001), indicating that the educational intervention successfully changed students' understanding and attitudes towards nutritional information Conclusion: This program not only provides short-term impacts in the form of increased knowledge but also encourages changes in students' attitudes towards previously believed nutritional myths without scientific basis.